HerMES: Halo occupation number and bias properties of dusty galaxies from angular clustering measurements - Cooray, A; Amblard, A; Wang, L; Arumugam, V; Auld, R; Aussel, H; Babbedge, T; Blain, A; Bock, J; Boselli, A; Buat, V; Burgarella, D; et al. (2010)
We measure the angular correlation function, w(θ), from 0.5 to 30 arcmin of detected sources in two wide fields of the Herschel Multi-tiered Extragalactic Survey (HerMES). Our measurements are consistent with the expected clustering shape from a population of sources that trace the dark matter density field, including non-linear clustering at arcminute angular scales arising from multiple sources that occupy the same dark matter halos. By making use of the halo model to connect the spatial clustering of sources to the dark matter halo distribution, we estimate source bias and halo occupation number for dusty sub-mm galaxies at z ∼ 2. We find that sub-mm galaxies with 250 μm flux densities above 30 mJy reside in dark matter halos with mass above (5±4)×1012 M⊙, while (14±8)% of such sources appear as satellites in more massive halos. © ESO 2010.